Dynamic analysis of executable code - Koh, You Jin. (2013)
This project explores the feasibility of using Intel Pin, a framework for creating tools, called Pintools, for dynamic binary analysis of executable. The report starts by introducing some the common vulnerabilities in software that can be easily exploited. Following that, it will discuss several different methods for analyzing software. It will then go on to give an introduction to Pin. The author will then presents the tools that are created to aid in software analysis, together with the discussion of the result. Finally, the feasibility and usefulness of Pin is discussed and areas of possible future development are outlines in the last chapter.